Experimental and numerical issues in the modelling of the mechanical behaviour of masonry - Lourenço, Paulo B. (1998)
In the last forty years an enormous growth in the development of numerical tools for structural analysis has been achieved. The use of such tools demands advanced testing in order to obtain the experimental characterisation of the mechanical behaviour of materials. This paper provides a review of displacement controlled experimental results and set-ups carried out in the last decade that are relevant for the purpose of sophisticated numerical modelling of masonry. The review includes testing under tension, shear and compression of units, mortar and small masonry samples, as well as, testing of masonry panels under uniaxial tension, uniaxial compression and biaxial stresses.An overview of possible approaches for the numerical modelling of masonry structures is also presented. This includes independent modelling of the units and joints, as well as modelling of masonry as an anisotropic continuum. Finally, recently developed sophisticated models and examples of their application are briefly presented.